Examining online citizenship behaviours in social network sites: a social capital perspective. Issue 9 (1st September 2016) - Son, Jung-Eun; Lee, So-Hyun; Cho, Eun-Young; Kim, Hee-Woong
ABSTRACT: As users have flocked to social network sites (SNSs), these sites have gained tremendous scale and concomitant social influence. This growth has come at the cost of social disruption caused by the posting of abusive comments and rumours that turn out to be false. To combat these negative phenomena, this study proposes SNS citizenship behaviour and examines it from the perspective of social capital theory. This study further examines how the key characteristics of SNS in terms of the concept of customer value affect social capital development in an SNS context. The test results explain that the structural, relational, and cognitive dimensions of social capital have significant direct and indirect effects on the SNS citizenship behaviour. These findings also explain that four key characteristics (exploration, communication support, playfulness, and responsiveness) of SNS affect the three dimensions of social capital. This study contributes to the literature in its establishment of the concept of SNS citizenship behaviour and examines it from the social capital theory perspective. Its findings have practical implications through its guidance on how to develop SNS features and manage these sites for the citizenship behaviour of their users, which are achievements for the harmonious and effective functioning of SNS.